Internalized Stigma in Persons With Mental Illness in Qatar: A Cross-Sectional Study - Kehyayan, Vahe; Mahfoud, Ziyad; Ghuloum, Suhaila; Marji, Tamara; Al-Amin, Hassen (Frontiers in Public Health, 2021)
Stigma impacts persons with mental illness (PWMI), their families and network of friends, the public and health care professionals. Stigma is a major barrier for PWMI to seeking treatment, which contributes to the burden of disease, disability, and mortality. Research on stigma is relatively scant in the Middle East region and particularly in Qatar. To address stigma effectively in each culture, it is essential to study its nature in the context where the PWMI experience stigma. The purpose of this study was to assess the prevalence of internalized stigma in PWMI in Qatar. A cross-sectional study of PWMI receiving outpatient mental health services in Qatar was done. We interviewed 417 PWMI using a modified 18-item version of the short form of the Internalized Stigma of Mental Illness (ISMI) Scale. Descriptive and regression models were used to analyze the data. The Cronbach alpha for the modified 18-items ISMI was 0.87. Participants' average score on this scale was 2.07 ± 0.38 with 41 (9.8%) of them scoring more than 2.5 which is considered “high” stigma score. In multivariate logistic regression, high stigma (modified ISMI score >2.5) was significantly higher among PWMI with no formal education and among those who reported lower levels of social support. The reported levels of internalized stigma in this vulnerable population of Qatar fall at the lower spectrum reported worldwide. An anti-stigma education program designed for the context of Qatar emphasizing on education and support for PWMI may be conducive to creating an all-inclusive society.